ANRIL: A lncRNA at the CDKN2A/B Locus With Roles in Cancer and Metabolic Disease - Kong, Yahui; Hsieh, Chih-Heng; Alonso, Laura C. (Frontiers in Endocrinology, 2018)
The CDKN2A/B genomic locus is associated with risk of human cancers and metabolic disease. Although the locus contains several important protein-coding genes, studies suggest disease roles for a lesser-known antisense lncRNA encoded at this locus, called ANRIL. ANRIL is a complex gene containing at least 21 exons in simians, with many reported linear and circular isoforms. Like other genes, abundance of ANRIL is regulated by epigenetics, classic transcription regulation, splicing and post-transcriptional influences such as RNA stability and microRNAs. Known molecular functions of ANRIL include in cis and in trans gene regulation through chromatin modification complexes, and influence over microRNA signaling networks. Polymorphisms at the ANRIL gene are linked to risk for many different cancers, as well as risk of atherosclerotic cardiovascular disease, bone mass, obesity and type 2 diabetes. A broad array of variable reported impacts of polymorphisms on ANRIL abundance, splicing and function suggests that ANRIL has cell-type and context-dependent regulation and actions. In cancer cells, ANRIL gain of function increases proliferation, metastasis, cell survival and epithelial-mesenchymal transformation, whereas ANRIL loss of function decreases tumor size and growth, invasion and metastasis, and increases apoptosis and senescence. In metabolic disease, polymorphisms at the ANRIL gene are linked to risk of type 2 diabetes, coronary artery disease, coronary artery calcium score, myocardial infarction and stroke. Intriguingly, with the exception of one polymorphism in exon 2 of ANRIL, the SNPs associated with atherosclerosis and diabetes are non-overlapping. Evidence suggests that ANRIL gain of function increases atherosclerosis; in diabetes, a risk-SNP reduced the pancreatic beta cell proliferation index. Studies are limited by the uncertain relevance of rodent models to ANRIL studies, since most ANRIL exons do not exist in mouse. Diverse cell-type-dependent results suggest it is necessary to perform studies in the relevant primary human tissue for each disease. Much remains to be learned about the biology of ANRIL in human health and disease; this research area may lead to insight into disease mechanisms and therapeutic approaches.